Analisis Perbandingan Pemberian Kredit Pemilikan Rumah (KPR) pada Bank Konvensional dengan Pembiayaan Murabahah (KPR) pada Bank Syariah - Satria, Muhammad Rizal; Setiani, Tia (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2018)
This research tries to compare financing system of housing credit amongs to common bank and sharia bank. The purpose of this comparation is to know the differences of financing system of housing credit by Bank Jabar Banten (BJB) and Bank Jabar Syariah which used to be sample. People only know if common bank used interest as rates in return and sharia bank did not use it. The factors will be compared are conditions apply, proccess of housing credit applied, akad or initial requirements, calculation of installments, and treatment of customers who late on paying or paying before the time.